2001
DOI: 10.1038/89289
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-mediated enhancement of DNA-raised immune responses by mutant caspases

Abstract: Apoptotic bodies can be used to target delivery of DNA-expressed immunogens into professional antigen-presenting cells (APCs). Here we show that antigen-laden apoptotic bodies created by vectors co-expressing influenza virus hemagglutinin (HA) or nucleoprotein (NP) genes and mutant caspase genes markedly increased T-cell responses. Both CD8 and CD4 T-cell responses were affected. The adjuvant activity was restricted to partially inactivated caspases that allowed immunogen expression before the generation of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 21 publications
4
72
1
Order By: Relevance
“…Both possibilities may lead to the generation and uptake of apoptotic vesicles or free antigen by professional antigen presenting cells and thus contribute to an enhancement of antigen-specific humoral and cellular immune responses. This hypothesis would be in accordance with the observations by others reporting that the induction of apoptosis significantly promotes the stimulation of immune responses towards per definition cytoplasmic antigens [37,38]. Accordingly, there is clear evidence suggesting that the induction of CTL and IFN-␥ producing T cells may be supported in all cases-and independent from our in vitro findings demonstrating cytoplasmic location of GagMyr − and p24-by cross-priming events via antigens in vivo [21,39].…”
Section: Discussionsupporting
confidence: 93%
“…Both possibilities may lead to the generation and uptake of apoptotic vesicles or free antigen by professional antigen presenting cells and thus contribute to an enhancement of antigen-specific humoral and cellular immune responses. This hypothesis would be in accordance with the observations by others reporting that the induction of apoptosis significantly promotes the stimulation of immune responses towards per definition cytoplasmic antigens [37,38]. Accordingly, there is clear evidence suggesting that the induction of CTL and IFN-␥ producing T cells may be supported in all cases-and independent from our in vitro findings demonstrating cytoplasmic location of GagMyr − and p24-by cross-priming events via antigens in vivo [21,39].…”
Section: Discussionsupporting
confidence: 93%
“…3 'Survival gene' Bcl-xl was reported to be critical in DC survival and in the magnitude of generated immune responses. 17,19 Owing to the possibilities of apoptosis of antigen-bearing somatic cells presentation to CD8+ T cells by local DCs and Bcl-xl-induced tumorgensis, [21][22][23]25 prolonging specifically DC survival in vivo may be an attractive strategy to improve T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, several studies have demonstrated that induction of apoptosis could improve DNA vaccine potential. [21][22][23] It was proposed that dying antigen-expressing somatic cells would become attractive targets for infiltrating local DCs and presenting to CD8+ T cells through crosspriming. 24 It raises a possibility that delivery of Bcl-xl DNA into antigen-expressing somatic cells may limit antigen resources especially in crosspriming, which is critical in inducing antigen-specific CD8+ T-cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…This may modulate the uptake of antigen complexes that are packed in the dying cells, thus modifying tolerance to foreign antigens [31]. This finding may help to explain the data gathered by Sasaki et al [13,14] who showed that "bland" apoptosis can elicit enhanced immune responses. The rabies virus glycoprotein is the main viral antigen.…”
Section: Discussionmentioning
confidence: 86%
“…In other systems, antigens produced by apoptotic cells increase the immunogenicity of the antigen [9,10]. Apoptotic bodies containing the antigen of interest have been obtained by different means such as enforced expression of Fas, cytochrome C, BAX or caspases [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%